(untitled) (Journal of Environmental Science and Natural Resources, 2015)
An attempt was made to explore correlation between climate variables and Kala-azar prevalence at four highly affected districts in Bangladesh: Mymensingh, Tangail, Pabna, and Rajshahi. The climate variables included were temperature, rainfall and relative humidity. With the rise of yearly average humidity in Mymensingh, Tangail and Rajshahi districts Kala-azar prevalence was significantly increased and with the rise of yearly total rainfall positive but not significant correlation was observed in Mymensingh,Tangail and Rajshahi. In Mymensingh negative correlation was found with yearly average maximum and minimum temperature. Positive association with yearly total rainfall in Mymensingh, Pabna & Rajshahi and yearly average minimum temperature in Rajshahi and yearly average maximum temperature in Tangail was observed. The prevalence of the disease was found to have negative correlation with yearly average maximum temperature in both Pabna & Rajshahi, yearly average minimum temperature in both Tangail & Pabna and yearly total rainfall in Tangail. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22045 J. Environ. Sci. & Natural Resources, 6(1): 79-87 2013